Advancements in cellular immunotherapy: overcoming resistance in lung and colorectal cancer - Qin, Lijuan; Li, Yuan; Liu, Juan; An, Xiaoqin (Frontiers in Immunology, 2025)
Immunotherapy has revolutionized cancer treatment, offering hope for patients with otherwise treatment-resistant tumors. Among the most promising approaches are cellular therapies, particularly chimeric antigen receptor T-cell (CAR-T) therapy, which has shown remarkable success in hematologic malignancies. However, the application of these therapies to solid tumors, such as lung and colorectal cancers, has faced significant challenges. Tumor resistance mechanisms—ranging from immune evasion, antigen loss, and immune checkpoint upregulation, to tumor microenvironment immunosuppression—remain major obstacles. This mini-review highlights the latest advancements in tumor immunotherapy, with a focus on cellular therapies, and addresses the resistance mechanisms that hinder their effectiveness in lung and colorectal cancers. We examine the evolution of CAR-T cell therapy, as well as the potential of engineered natural killer (NK) cells and macrophages in solid tumor treatment. The review also explores cutting-edge strategies aimed at overcoming resistance, including combination therapies, gene editing technologies, and nanotechnology for targeted drug delivery. By discussing the molecular, cellular, and microenvironmental factors contributing to resistance, we aim to provide a comprehensive overview of how these challenges can be overcome, paving the way for more effective, personalized immunotherapies in lung and colorectal cancer treatment.